A System of Morphometry - Olson, F. C. W. (The International Hydrographic Review, 2018)
This system is based on a square lattice superimposed on a map of the lake. Area, volume, depth distribution, length of shoreline and other morphometric concepts are derived simply. The system has the advantage that the precision of the measurements can be estimated. The method is simple, rapid and requires no special instruments.